2019
DOI: 10.1111/andr.12634
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of sperm maturation and capacitation due to diet‐dependent cholesterol overload

Abstract: Background: Lipid metabolic disorders (dyslipidemia) are constantly increasing in occidental societies and lead to the development of pathologies such as obesity, diabetes, and metabolic syndrome. It has been demonstrated that dyslipidemia can alter the reproductive function. Animal models have recently been used to show that the offspring of dyslipidemic males could also develop such pathologies and that the transgenerational transmission involved post-testicular sperm maturation. These data targeted the esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…It is present in human [52] and mouse epididymosomes (M. Whitfield, personal communication) and it is a major protein for sperm functions, as described in bovine studies [56]. We previously showed that disorders of the mouse sperm capacitation process could be associated with decreased sperm YWHAZ content in a pathological situation such as dyslipidemia [57].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is present in human [52] and mouse epididymosomes (M. Whitfield, personal communication) and it is a major protein for sperm functions, as described in bovine studies [56]. We previously showed that disorders of the mouse sperm capacitation process could be associated with decreased sperm YWHAZ content in a pathological situation such as dyslipidemia [57].…”
Section: Discussionmentioning
confidence: 98%
“…It is present in human [ 52 ] and mouse epididymosomes (M. Whitfield, personal communication) and it is a major protein for sperm functions, as described in bovine studies [ 56 ]. We previously showed that disorders of the mouse sperm capacitation process could be associated with decreased sperm YWHAZ content in a pathological situation such as dyslipidemia [ 57 ]. As YWHAZ function is central for male fertility, if the ATS YWHAZ protein contains an ATS -specific epitope with immunogenic potential, it could be considered as a contraceptive antigen worth testing.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies investigated the relationships between plasma cholesterol and sperm epididymal maturation/function and found that the epididymis is a target of lipid‐induced infertility, and its function is altered by dietary cholesterol overload (Ouvrier et al, 2011; Saez et al, 2019). In this study, we investigated the effects of administering an HFD for 5 weeks on the epididymis of rats.…”
Section: Discussionmentioning
confidence: 99%